MYCOBACTERİUM TUBERCULOSİS SUŞLARININ MAJÖR ANTİTÜBERKÜLOZ İLAÇLARA DUYARLILIĞIN BACTEC 460 TB SİSTEMİ İLE TESPİT EDİLMESİ - ATALAR, DEMET (Fırat Üniveristesi, 2004)
Tüberküloz iyileşme süresi uzun süren bir infeksiyon hastalığıdır.Gelişmekte olan ülkelerde % 95 oranında yeniden ortaya çıkmakta ve dünya popülasyonunun üçte birini etkilemektedir. 1995 - 2005 yıllan arasında, bu oranların 8.8 milyondan 1 1.9 milyona yükselişi geleceği tehdit etmektedir. Özellikle son 15 yılda tüm dünyada tüberküloz vakalarının sayısında önemli bir artış meydana gelmiştir. Buna paralel olarak da çoklu ilaç direncine sahip Mycobacterium tuberculosis suşlarında da belirgin bir artış olduğu gözlenmiştir. Bundan dolayı bütün tüberküloz hastalarında, hızlı direnç testleri zorunlu olarak yapılmalıdır. Bu çalışmada majör antitüberküloz ilaçlardan izoniazit, rifampin streptomisin ve ethambutolün akciğer tüberkülozlu hastaların balgam, BOS, AMS ve idrar örneklerinden izole edilen 27 susun invitro etkinlikleri Bactec metoduyla araştırılmıştır. Duyarlılık testlerinde izolatların % 21'i izoniazide, % 25 'i rifarnpine, % 37'si ethambutole ve % 17'si streptomisine dirençli olarak saptanmıştır. Ayrıca 27 susun 4'ünde en az rifampin ve izoniazide karşı direnç olarak adlandırılan çok ilaca direnç tespit edilmiştir. Bu direnç oranlan, bölgemizde çok ilaca dirençliliğin var olduğunu göstermiştir. Anahtar Kelimeler : Mycobacterium tuberculosis, majör antitüberküloz ilaçlar, Bactec test yöntemi

Tuberculosis is a chronic infectious disease that requires long term threapy to recovery. It affects one third of the world's population and 95 % of the diseases durden is burn by developing countries. This situation is likely to deteriorate in future with annual disease expected to be risen from 8.8 and 1 1.9 million between 1995 and 2005. There is significant increase in the number of tuberculosis cases in last 15 years, all over the world. At the same time, multidrug resistant Mycobacterium tuberculosis strains have increased significantly. Therefore, rapid antimicrobial susceptibility tests should be used to achieve to efficient and appropriate therapy for all of patients diagnosed with tuberculosis. In this study, in vitro activities of isoniazide, rifampisin, streptomycin and ethambutole, that are the major antituberculose agents, were investigated with Bactec System for 27 Mycobacterium tuberculosis strains, isolated from sputum, CSF, gastric lavage and urine samples of pulmonary tuberculosis patients. Susceptibility tests have yielded that 21 % of the isolates were resistant to isoniaside, 25 % were to rifampisin, 37 % were to etambutole and 17 % were to steptomycine. Additionally, 4 of 27 (14.81 %) isolates were found to be multiresistant mat were resistant to at least rifampisin and izoniaside. These resistance patterns showed that Mycobacterium tuberculosis strains isolated from the patients who are living in our region, associated with multiple drug resistance. Key words: Mycobacterium tubeculosis, major antituberculosis agents, Bactec test method.
Susceptibility of major antitüberculosis agents on Mycobacterium tuberculosis strains using by bactec 460 TB system
Keywords: Mikrobiyoloji; Microbiology